Brain Gym Untuk Meningkatkan Kognitif Dalam Motivasi Belajar Pada Siswa Sekolah Dasar (Masa Bencana Pandemic Covid-19) - Heru Suwardiyanto; Sandy Kurniajati (Jurnal Empathy Pengabdian Kepada Masyarakat, 2021)
Background: Students experience learning barriers during online learning methods. Online learning can also reduce children's learning motivation at school during the COVID-19 Pandemic Disaster. Cognitive impairment due to distance education can affect memory conditions and will also affect their future. The thinking process in elementary school students is very important in thinking, developing creativity in being creative. The aim in this activity of community service is to provide health education about brain gym to students. Methods: The devotee gave a brain gym video to the respondents and after one month an evaluation of learning motivation was carried out. Brain gym videos contain interactive brain gym procedures with short and clear explanations. Results: The results of community service were found that male service participants were 63.5%, while there were 36.5% female. The most participants were 11 years old by 23.1%. After being given a brain gym educational video, the most students had a fairly good cognitive learning as much as 51%, and those who had a good cognitive learning were 39,4%. The most participants were 11 years old by 23.1%. After being given a brain gym educational video, the most students had a fairly good learning motivation as much as 44.2%, and those who had a good learning motivation were 37.5%. Conclusion: Brain gym procedures can increase cognitive learning motivation and also improve students' cognitive abilities.